Pengaruh Beauty Influencer, Word of Mouth dan Brand Image Terhadap Keputusan Pembelian Produk Kosmetik Wardah pada Mahasiswa Prodi Pendidikan Ekonomi Universitas Bhinneka PGRI - Wikan, Dyah; Hastuti, Maria Agatha Sri Widyanti (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Many women are starting to open their eyes to the need to care for and beautify themselves, skin care products and make-up are needed to support their appearance to be more presentable and appropriate when meeting other people. The purpose of this study was to determine the effect of Beauty Influencers, Word Of Mouth and Brand Image on Purchasing Decisions for Wardah products for Economics Education Study Program Students at Bhinneka PGRI University. The sample of this study were 64 female students of Economics Education Study Program in semester VI and VIII who were selected through Purposive Sampling with quantitative research type. Based on the results of the t test, Beauty Influencer has no effect on Purchasing Decisions for Wardah products with a tcount value of -0.271 < t table 2,000, Word of Mouth affects Purchasing Decisions with a tcount value of 2.644 > t table 2,000, Brand Image affects Purchasing Decisions with a tcount value of 6.880 > t table 2,000. Simultaneously Beauty Influencer, Word Of Mouth and Brand Image have a significant influence with an Fcount value of 47.627> Ftable of 3.150. The coefficient of determination is 68.9% of the Purchasing Decision variable (Y) is influenced by the Beauty Influencer variable (X1), Word of Mouth (X2), Brand Image (X3). Meanwhile, 31.1% is influenced by other factors outside the variables in this study.